Human serum metabolomic analysis reveals progression for high blood pressure in type 2 diabetes mellitus. Issue 1 (28th October 2021) - Zhang, Yin; Zhao, Heru; Liu, Bin; Shu, Haiyang; Zhang, Lulu; Bao, Mei; Yi, Wenjun; Tan, Yong; Ji, Xinyu; Zhang, Chi; Zhao, Ning; Pang, Guoming; et al.
Abstract : Introduction: Type 2 diabetes mellitus (T2DM) is one of the most ordinary metabolic disorders and manifests as a high blood sugar level; 80%–90% of patients with T2DM will develop high blood pressure (HBP), which exacerbates irreversible organ damage. Understanding the metabolic basis of HBP is essential to facilitating early diagnosis and prompt treatments of diabetic complications. Research design and methods: 34 patients who originally had T2DM and then developed HBP within 1 year were selected from physical examination participants. Using ultrahigh-performance liquid chromatography quadrupole time-of-flight metabolomic analysis, we compared the metabolomic profile of patients with 30 healthy controls. The results showed a clear discrimination in metabolomic profiles between T2DM and T2DM+HBP when employing orthogonal projection to latent structure with discriminant analysis with electrospray ionization modes. Results: Eight differential metabolites changed significantly during disease progression, among which L-isoleucine, L-glutamic acid, pyroglutamic acid and linoleic acid decreased, while sphinganine, Cer(d18:0/16:0), Cer(d18:0/18:0), and citric acid increased. These metabolites are associated with the γ-glutamyl cycle, tricarboxylic acid cycle, and ceramide metabolism. Conclusions: These novel serum biomarkers may improve the management of T2DM and HBP complications, thus reducing the use of incorrect medical care.